Socialization of Online Passport Queue Service Application of the Directorate General of Immigration, Ministry of Law and Human Rights - Gunawan Gunawan; Usman Mutaqin (Jurnal Abdimas Imigrasi, 2020)
Passports have a role not only limited to the requirements to leave the territory of Indonesia, but the ownership of the passport must be accounted for. The problem is often complained by many people in applying for a passport (the applicant) is the queue which takes a long time and feels complicated in implementation. Now the Directorate General of Implications of the Ministry of Law and Human Rights is innovating by creating an APAPO (Online Passport Queue Application). This application is expected to be an answer problems in applying for a passport for the applicant. This online passport registration is related to how operate the APAPO application, and see when the applicant's schedule can come to the nearest immigration office. This socialization was carried out in the Tasikmalaya region, West Java, bearing in mind that the Tasikmalaya area had a considerable potential of Indonesian Migrant Workers (TKI) and the Immigration Office in charge of several Cities and Regencies, including: Tasikmalaya District, Tasikmalaya City, Regencies Ciamis, Banjar City and Garut Regency which cover 108 (one hundred and eight) districts. Community Service regarding passport registration at the immigration office is by way of socialization regarding online passport registration with the following steps: (1) Financing the importance of passports for Indonesian citizens (2) Developing procedures for registering online passport queues (3) Training for opening applications online passport queue service.